One Hundred Years of “Group Psychology and The Analysis of The Ego”: With Addendum - Sergio Benvenuto (EJP import test, 2020)
Contribution to the Webinar “Subject and Masses”, 2021, https://www.journal-psychoanalysis.eu/webionar-soggetto-e-masse/ 02/12/2021